Legal Environment, Technological Innovation, and Sustainable Economic Growth - Zhao, Yidan (Frontiers in Psychology, 2022)
The productivity gains generated by innovation are the root cause of long-term economic growth. Different from relevant researches, this paper discusses the decisive role of market activity and legal environment on regional technological innovation behavior from the perspective of technology trade and patent protection, and emphasizes the theoretical significance of market and legal system from a more general perspective. The empirical research result show that: (1) Technology market transaction volume has a "demonstration effect" on regional innovation activities. The greater the technology trade volume, the greater the incentive to regional innovation activities, the greater the number of regional patents; (2) Intellectual property protection has a "protection effect" on regional innovation activities. The higher the protection intensity is, the greater the incentive is to regional innovation activities and the greater the number of regional patents.